2019
DOI: 10.1051/e3sconf/201914008014
|View full text |Cite
|
Sign up to set email alerts
|

Consequence assessment of explosions for fuel-air mixtures at hazardous production facilities

Abstract: The article reviewed one of the known accidents with explosions of fuel assemblies both in domestic and foreign enterprises, and analyzed the causes of its occurrence. With the help of several computational methods, the sizes of the zones of air-shock wave (ASW) were determined and compared with the “real” data, and situational plans with zones of destruction were constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…If T shows class values, the probability of a class can be computed using (3). The entropy value of the classes is computed using (4).…”
Section: Decision Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…If T shows class values, the probability of a class can be computed using (3). The entropy value of the classes is computed using (4).…”
Section: Decision Treesmentioning
confidence: 99%
“…It has been reported that young workers have a higher non-fatal accident rate than older workers [2,3]. In order to create and maintain a safe working environment, hazards that may occur at workplaces should be identified and it is necessary to effectively monitor potential risks and give priority to preventive activities [4].…”
Section: Introductionmentioning
confidence: 99%